Structural, electronic, mechanical, and thermodynamic properties of Cu–Ti intermetallic compounds: First-principles calculations. (1st September 2022) - Xu, Yang; Tian, Meiling; Hu, Changyi; Han, Zhaohui; Zhou, Shenggang; Cao, Yong
Abstract: In this study, the structural, electronic, mechanical, and thermodynamic properties of Cu–Ti intermetallic compounds (Cu4 Ti, Cu2 Ti, Cu3 Ti2, Cu4 Ti3, CuTi, and CuTi2 ) were predicted using first-principles calculations. The formation enthalpy results show that all Cu–Ti intermetallic compounds are thermodynamically stable, and the thermodynamic stability decreased in the order CuTi > Cu4 Ti3 > CuTi2 > Cu2 Ti > Cu4 Ti > Cu3 Ti2 . The elastic constants and polycrystalline moduli were obtained using stress-strain method and Voigt-Reuss-Hill approximation. The results show that all Cu–Ti intermetallic compounds are mechanically stable. The anisotropic elasticity increased in the order Cu4 Ti < CuTi2 < CuTi < Cu2 Ti < Cu4 Ti3 < Cu3 Ti2 . The density of states verified that the Cu–Ti chemical bonds are formed by Cu-3d and Ti-3d hybridizations. In addition, the effects of high pressure (0–40 GPa) and temperature (0–1100 K) on the thermodynamic properties of these Cu–Ti intermetallic compounds were systematically studied based on the Quasi-harmonic Debye model. The isothermal bulk modulus and Debye temperature of these Cu–Ti intermetallic compounds increased with increasing pressure and decreasing temperature. The minimum thermal conductivity has the same order as the formation enthalpy. Highlights: Structural, electronic, mechanical, and elastic anisotropy were comparatively studied. Thermodynamic properties were systematically analyzed from the Quasi-harmonic Debye model. k min decreases in the order CuTi > Cu4 Ti3 > CuTi2 > Cu2 Ti > Cu4 Ti > Cu3 Ti2 .